2013
DOI: 10.1186/1479-5876-11-142
|View full text |Cite
|
Sign up to set email alerts
|

CDC20 overexpression predicts a poor prognosis for patients with colorectal cancer

Abstract: BackgroundThe cell division cycle 20 homolog (CDC20) is an essential cofactor of the anaphase-promoting complex (APC/C). CDC20 overexpression has been detected in many types of human cancers; however, its clinical role in colorectal cancer remains unknown.MethodsWestern blotting and immunohistochemistry were used to compare CDC20 expression in adjacent non-cancerous, cancerous and liver metastatic tissues as well as in colon cancer cell lines and normal colon epithelial cell lines. Additionally, the correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
109
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(115 citation statements)
references
References 24 publications
6
109
0
Order By: Relevance
“…CDC20 expression was detected in the nuclei and/or cytoplasm of the tumor cells as shown in previous studies [23,25,26,36,38,39]. CDC20 overexpression was detected in 55.7 % while low CDC20 expression was found in 44.3 % of all examined malignant tumors.…”
Section: Cdc20 Immunohistochemical Expression In Malignant Tumorsmentioning
confidence: 56%
See 3 more Smart Citations
“…CDC20 expression was detected in the nuclei and/or cytoplasm of the tumor cells as shown in previous studies [23,25,26,36,38,39]. CDC20 overexpression was detected in 55.7 % while low CDC20 expression was found in 44.3 % of all examined malignant tumors.…”
Section: Cdc20 Immunohistochemical Expression In Malignant Tumorsmentioning
confidence: 56%
“…Positive CDC20 expression was observed in the breast, colon, endometrium, head and neck, kidney, lung, ovary, pancreas, prostate, and testis. Previous studies reported positive CDC20 expression in the normal/non-neoplastic epithelial cells of Graph 1 CDC20 immunohistochemical expression in normal/non-neoplastic tissues and primary malignant tumors from multiple organs the colon, stomach, head and neck, and pancreas (23,26,27,36), while others reported that CDC20 expression was negative in normal/non-neoplastic epithelial cells of the bladder, breast, cervix, liver, and lung [24,25,[37][38][39]. Our comprehensive study corroborated and expanded these observations as we found negative CDC20 expression in normal/non-neoplastic tissues from the bladder, cervix, liver, stomach, and thyroid.…”
Section: Cdc20 Immunohistochemical Expression In the Normal/non-neoplmentioning
confidence: 99%
See 2 more Smart Citations
“…APC activation is required for anaphase initiation and mitosis exit [10]. In addition, it was recently found that CDC20 overexpressed in many types of human cancers, including human nonsmall cell lung cancer, pancreatic cancer, gastric cancer, colorectal cancer, glioma, breast cancer, and oral cancer [10][11][12][13][14][15][16]. It suggests that CDC20 maybe play an important role in the mechanism of the occurrence and development of glioma.…”
Section: Discussionmentioning
confidence: 99%